Morphology and Sequencing of Myxobolus koi DNA that Infects Koi fish (Cyprinus carpio) in Blitar Regency - Rachmat Noer Soelistyoadi; A.D. Nurekawati; D. Setyawati (Airlangga University, 2020)
Myxobolus koi is a type of myxospore parasite that infects many fresh ornamental fish, this disease is also called myxobolusis. Currently there are 29 species of Myxobolus that have been identified to infect Cyprinus carpio, with 17 of them infecting gills, so it will be difficult to determine the type of Myxobolusis. This study aims to identify Myxobolus species that infect Cyprinus carpio koi fish based on conventional and molecular analysis. Myxobolus spores obtained from Blitar Regency microscopically have spores length of 11-14 íŽ¼m with an average of 12.82 ± 0.75 íŽ¼m and width of 7-8 íŽ¼m with an average of 7.09 ± 0.84 íŽ¼m, while the size capsules have a length of 7-8 íŽ¼m with an average of 7.36 ± 0.497 íŽ¼m and a width of 2-3 íŽ¼m with an average of 2.64 ± 0.49 íŽ¼m n = 10. Electrophoresis results of clinically infected fish Myxobolus koi appeared band (band) at 2000 bp, sequencing DNA Myxobolus koi parasites that infect koi fish (Cyprinus carpio) in Blitar have the highest similarity (percent identity) with the sample code KT.240127.1, namely on Myxobolus koi which infects Rainbow trout (Oncorhynchus mykiss) in Southwest China. The closest genetic distance of the Myxobolus koi blitar sample to the Myxobolus koi sample in koi fish (Cyprinus carpio) with sample code FJ841887.1 and Myxobolus koi in rainbow trout (Oncorhynchus mykiss) with sample code KT240127.1. at the same value 0.273.Keyword : Myxobolus koi, koi (Cyprinus carpio), PCR, Sequencing.